A preliminary vulnerability assessment for Ísafjörður, Iceland : coastal management options to reduce impacts of sea-level rise and storm surges - Meidinger, Manuel (2011)
Climate change science argues that by the end of the 21st century, the global mean sea-level rise may easily exceed 1 metre, possibly accompanied by an increase in storm intensity. Although climate change is a global phenomenon, its impacts vary greatly according to scale and geographic region. This study took into account the United Nations’ recommendations and the research objectives stated by the Icelandic Ministry of the Environment, and conducted a preliminary coastal vulnerability assessment for Ísafjörður, located in the Westfjords of Iceland. A digital elevation model was created from 1 metre contour lines and used for GIS analysis. Due to uncertainty on future projections of sea-level rise, three equally probable normative scenarios (temperature and sea-level worlds) were constructed. Two scenarios explore the variation in regional sea-level at the case study area under fixed global temperature targets (2 degree world, 3 degree world). The third scenario assumes an increase in mean global seal-level of 1 metre by the end of the current century (1 metre sea-level rise world). In this work, the potential economic damages and expected loss of life from local storm surges were assessed. Assuming that rising sea-levels will add to the height of current storm dynamics, coastal options to deal with the threat of sea-level rise were proposed. This addresses the need to move beyond the identification of hot spots of vulnerability to propose measurable costal adaptation strategies to sea-level rise and storm surge impacts in Ísafjörður. Results reveal that socio-economic impacts from sea-level rise and storm surges are expected to increase in Ísafjörður, more notably towards the end of the 21st century. Nevertheless, Ísafjörður possesses the time and a range of costal adaptation options to prepare for the impacts. In the case of potential loss of life, the coastal system thresholds were calculated and maximum allowed population growth rates were provided. Mitigation of monetary impact costs by prioritizing ...